Charter schools : hope or hype? - Buckley, Jack, 1972- (Princeton University Press, 2007)
Over the past several years, privately run, publicly funded charter schools have been sold to the American public as an education alternative promising better student achievement, greater parent satisfaction, and more vibrant school communities. But are charter schools delivering on their promise? Or are they just hype as critics contend, a costly experiment that is bleeding tax dollars from public schools? In this book, Jack Buckley and Mark Schneider tackle these questions about one of the thorniest policy reforms in the nation today. Using an exceptionally rigorous research.